2002
DOI: 10.1254/jjp.89.356
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of M5 Muscarinic Receptor in the Enhancing Actions of the Novel Gastroprokinetic Agent Z-338 on Nifedipine-Sensitive Voltage-Dependent Ca2+ Currents in Guinea Pig Stomach

Abstract: ABSTRACT-We investigated the effects of the novel gastroprokinetic agent Z-338 (N-(N'-N'-diisopropylaminoethyl)-[2-(2-hydroxy-4,5-dimethoxybenzoylamino)-1,3-thiazole-4-yl] carboxyamide monohydrochloride trihydrate) on L-type voltage-dependent Ca 2+ currents (ICa) in guinea pig gastric myocytes by using the whole-cell patch clamp technique. Bath-applied acetylcholine (ACh) produced biphasic effects on ICa, i.e., enhancement (1 -100 nM) and inhibition (1 -100 mM), both of which were abolished by pretreatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…All these findings are consistent with the view that Z-338 facilitates excitatory neuroeffector transmission in the stomach by increasing ACh release from cholinergic nerve terminals via inhibition of pre-junctional M1-and M2-mAChR or nAChR. In addition to these pre-junctional actions, Z-338 potentiates L-type voltage-dependent Ca 2+ currents (ICa) possibly through activation of M5-like-mAChR in guinea pig gastric myocytes (Morita et al, 2002). These pre-and post-synaptic effects taken together would explain the actions of Z-338 to enhance spontaneous contractions without changing the basal muscle tone of the stomach, and suggest that Z-338 could improve gastric emptying in patients with functional dyspepsia.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…All these findings are consistent with the view that Z-338 facilitates excitatory neuroeffector transmission in the stomach by increasing ACh release from cholinergic nerve terminals via inhibition of pre-junctional M1-and M2-mAChR or nAChR. In addition to these pre-junctional actions, Z-338 potentiates L-type voltage-dependent Ca 2+ currents (ICa) possibly through activation of M5-like-mAChR in guinea pig gastric myocytes (Morita et al, 2002). These pre-and post-synaptic effects taken together would explain the actions of Z-338 to enhance spontaneous contractions without changing the basal muscle tone of the stomach, and suggest that Z-338 could improve gastric emptying in patients with functional dyspepsia.…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, our recent study indicates that rat stomach receives efferent neural input from AP and electrical stimulation of AP neurons relaxes the stomach in rat, thereby suggesting that some functional roles of AP neurons in the regulation of gastric motility (Kawachi et al, 2008). Z-338 has well documented excitatory but not inhibitory action on stomach motility through the peripheral autonomic nervous system (Ueki et al, 1998;Nakajima et al, 2000;Kanemoto et al, 2002;Morita et al, 2002). The actions of Z-338 on central and peripheral autonomic nervous system, taken together, would therefore explain the observations that Z-338 induces postmeal relaxation and improve postprandial fullness in patients with functional dyspepsia (Tack et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression rate of m5 is less than 2-5% of total brain mAChR protein, and its physiological role in vivo is still indistinct [11]. A few studies have shown that m5 is involved in an increase of [Ca 2+ ] i in rat glomerular podocytes [33], the contraction of ciliary muscles in dog eye [7], and an enhancing action on the L-type Ca 2+ currents [32].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that such selective stimulation by acotiamide of postjunctional M 5 but not M 2 or M 3 receptors would explain how it enhances spontaneous rhythmic contractions of smooth muscle with little accompanying increase in the basal tension [18].…”
Section: Basic Pharmacology and Animal Researchmentioning
confidence: 99%